Redescription of the genus Cavernicola and the tribe Cavernicolini (Hemiptera: Reduviidae: Triatominae), with morphological and morphometric parameters - de Oliveira, Maria Angélica; de Souza, Rita De Cássia Moreira; Diotaiuti, Liléia (Zootaxa, 2007)
The genus Cavernicola Barber 1937 and the tribe Cavernicolini Usinger 1944 were originally described from a single species, C. pilosa Barber 1937. The description of C. lenti Barrett & Arias 1985 rendered inadequate certain diagnostic characteristics chosen for these taxa. These taxa and C. pilosa are redescribed here based on morphological and morphometric studies of the two species.